Preparation method of aluminum nitride powder with silicon dioxide coating layer

The formation of a silica cladding layer in the fluidized bed through fluidization modification technology solves the problem that the surface modification of aluminum nitride filler powder is difficult to enhance mechanical strength and improve coating uniformity, and achieves higher hydrolysis resistance and mechanical properties.

CN119505578APending Publication Date: 2025-02-25UNIV OF SCI & TECH BEIJING
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411602344.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, surface modification of aluminum nitride filler powder is mainly used to prepare hydrophobic coatings to resist hydrolysis, and it has failed to effectively enhance its mechanical strength and improve the thickness uniformity, durability and stability of the coating.

Method used

Using fluidization modification technology, the silicon dioxide precursor and oxygen source are introduced in the fluidized bed by spraying, and a covalent bonding reaction is carried out to form a uniform silicon dioxide coating layer, which improves the hydrolysis resistance and mechanical strength of the aluminum nitride powder.

Benefits of technology

The uniform coating and thickness control of the surface of aluminum nitride filler powder is achieved, which significantly improves its hydrolysis resistance and mechanical properties under high temperature and high humidity conditions, and enhances compressive, tensile and bending resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505578A_ABST
    Figure CN119505578A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of aluminum nitride powder with a silicon dioxide coating layer, and relates to the technical field of surface modification technologies of aluminum nitride filler powder. The preparation method of the aluminum nitride powder with the silicon dioxide coating layer comprises the following steps: carrying out surface pretreatment on AlN filler powder, carrying out drying treatment, carrying out silicon dioxide modification treatment on the AlN filler powder, and repeating and circulating the surface modification treatment to obtain the AlN filler powder coated with the silicon dioxide coating layer. Uniform coating and thickness control of the surface of the AlN filler powder can be achieved through the fluidization modification technology, the hydrolysis resistance of the AlN powder with the silicon dioxide coating layer is remarkably improved, the thermal interface material is compounded with an organic matter matrix, and the mechanical strength, compressive strength, bending strength and other performance of the thermal interface material can be enhanced; the method is simple and easy to operate, reduces dependence on harmful solvents, is green and environment-friendly, is low in cost and high in efficiency, and is beneficial to industrial large-scale production and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface modification technology of aluminum nitride filler powder, in particular to a method for preparing aluminum nitride powder with a silicon dioxide coating layer. Background Art

[0002] Thermally conductive aluminum nitride is an excellent ceramic material with high thermal conductivity, low thermal expansion coefficient and excellent electrical insulation properties. It is widely used in electronic devices, heat dissipation materials and other fields. In industries such as plastics, rubber and coatings, the performance of the filler directly affects the physical and mechanical properties of the material. However, thermally conductive aluminum nitride filler powder will undergo hydrolysis reaction in a humid environment or in water to produce aluminum hydroxide and ammonia. Hydrolysis may cause the mechanical strength and thermal conductivity of aluminum nitride to decrease. If aluminum nitride is used in electronic equipment or other sensitive components, hydrolysis may cause corrosion of circuit boards or other components, affecting the reliability of the equipment. Therefore, improving its hydrolysis resistance is the key to improving its application performance.

[0003] Traditional surface modification methods, such as surface coating technology, chemical modification and heat treatment, often have the following problems: 1) Insufficient adhesion. The coatings formed by many methods have weak bonding with the thermally conductive aluminum nitride surface and are easily detached during subsequent processing, resulting in performance degradation; 2) Uneven and incomplete thickness. Traditional modification technologies make it difficult to achieve uniform coating thickness on the powder surface, affecting the consistency and reliability of the material; 3) Harsh reaction conditions. Some modification methods require high temperatures or complex reaction conditions, which increases production costs and energy consumption.

[0004] For example, Chinese patent CN106586983A discloses a method for preparing aluminum nitride powder for thermal conductive filler, in which surface modification is performed by ball milling a coupling agent, anhydrous ethanol and an aluminum nitride sample. Although aluminum nitride powder with excellent hydrolysis resistance and good compatibility with polymer materials can be obtained, the wet ball milling modification results in an uneven shell thickness.

[0005] Chinese patent CN115637063A discloses a coating modification method for aluminum nitride powder and its application. The method can accurately control the coating layer of aluminum nitride powder by performing graded and differentiated fine coating modification treatment on aluminum nitride powder, and is applied to technical fields such as thermal conductive gel and thermal conductive silicone grease. The effective coating grafting rate refers to the ratio of the amount of polymer grafted on the surface of the particle by a specific method to the total mass of the particle. Obviously, the surface is coated with polymer, which is not suitable for use as a thermal conductive filler.

[0006] Chinese patent CN113474411A discloses a method for preparing aluminum nitride particles coated with silicon oxide and a method for preparing a heat dissipation resin composition. Although the method can obtain aluminum nitride particles coated with silicon dioxide, triethoxysilane is an organic silicon compound but not an organic siloxane. Therefore, in order to obtain silicon dioxide in the method, a heating temperature of more than 300°C is required, which consumes a lot of heat energy. Due to the agglomeration of aluminum nitride particles, it is not possible to evenly coat the surface of all aluminum nitride particles in an organic solution.

[0007] Chinese patent CN115011143A discloses a silicon dioxide coating layer and a preparation method thereof, which requires limited preparation of a dispersion liquid, adjusting the dispersion liquid to be alkaline, then adding a silicon source for reaction coating to form a first silicon film, and adjusting the dispersion liquid to be acidic to continue coating to form a second silicon film; therefore, the silicon dioxide coating layer is divided into two layers, and the control of its thickness uniformity is very difficult, and the possibility of uneven surface is very high. Summary of the invention

[0008] In order to solve the problem that the surface of aluminum nitride filler powder in the prior art is generally modified to prepare a hydrophobic coating to resist hydrolysis, most of the components of the hydrophobic coating are organic matter or polymers, and the modification is not considered to enhance the mechanical strength of the aluminum nitride filler, improve its compression, tension and bending resistance, and also does not consider the technical problems that the thickness uniformity, thickness control, durability, stability and other properties of the modified coating are difficult to control; Therefore, the present invention proposes a method for preparing aluminum nitride powder with a silicon dioxide coating layer, through fluidized modification technology, using the uniform coating effect of the fluidized bed, forming a uniform silicon dioxide film coating layer, thereby improving the hydrolysis resistance of aluminum nitride. This fluidized bed technology has great advantages in powder modification, and can achieve more uniform coating and modification effects. The method utilizes fluidized bed technology, can achieve uniform deposition under controllable conditions, and forms strong and firm covalent bonding through chemical reactions, significantly improving the adhesion and durability of the film coating layer. The technical scheme is as follows:

[0009] A method for preparing aluminum nitride powder having a silicon dioxide coating layer, the method for preparing aluminum nitride powder having a silicon dioxide coating layer comprises the following steps:

[0010] S1. Surface pretreatment of AlN filler powder: weigh an appropriate amount of high-purity AlN filler powder, mix the AlN filler powder with anhydrous ethanol to prepare an AlN suspension, place the suspension in an ultrasonic cleaning machine and start a cleaning process while ultrasonicating and stirring, and then perform vacuum filtration to obtain AlN filler wet powder;

[0011] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment to obtain AlN filler powder with clean surface;

[0012] S3, silica modification treatment of AlN filler powder: placing the cleaned AlN filler powder in S2 in a fluidized bed reactor, turning on a heating device to control the required fluidization temperature, introducing a silica precursor into the fluidized bed reactor by spraying and reacting under an inert atmosphere, and then introducing an oxygen source into the fluidized bed reactor through a gas input system to carry out a surface covalent bonding reaction of the AlN filler powder under an inert atmosphere to obtain silica-modified AlN filler powder;

[0013] S4, repeat and cycle S3: repeat the silica modification treatment of the AlN filler powder of S3 to the silica-modified AlN filler powder of S3, forming a silica coating layer of different thicknesses, uniform distribution and stable performance on the surface of the AlN filler powder, and obtaining AlN filler powder coated with the silica coating layer.

[0014] Optionally, the AlN filler powder in S1 has a particle size of 1-20 μm and a purity of 99.90-99.99%.

[0015] Optionally, the mass ratio of AlN filler powder to anhydrous ethanol in S1 is 1:(1.58-4.74).

[0016] Optionally, the ultrasonic parameters of the cleaning process in S1 are set as follows: ultrasonic temperature 25-35° C., ultrasonic time 10-20 min.

[0017] Optionally, the drying temperature in S2 is 50-75° C., the drying time is 2-4 hours, and the surface-cleaned AlN filler powder is spherical or quasi-spherical in shape, with a particle size of 1-20 μm and a water content of 0.05-0.2%.

[0018] Optionally, the silicon dioxide precursor in S3 is at least one of silicon tetrachloride, dimethylsilane and triethoxysilane, and the flow rate of the silicon dioxide precursor is 0.3-1 L / min, and the time is 3-6 min.

[0019] Optionally, the oxygen source in S3 is at least one of oxygen and water, and the oxygen source introduction flow rate is 0.3-1 L / min, and the time is 3-6 min.

[0020] Optionally, the inert atmosphere in S3 is at least one of nitrogen and argon, the time of inert gas introduction lasts from the beginning of fluidization to the end of fluidization, and the flow rate of inert gas introduction is 0.2-2L / min; the fluidization treatment temperature is 120-200°C, and the fluidization time is 100-980min.

[0021] Optionally, the silicon dioxide precursor and the oxygen source in S3 are successively introduced into the fluidized bed reactor through different independent delivery systems.

[0022] Optionally, the number of cycles mentioned in S4 is 15-80, the thickness of the silica coating layer is controlled to be 3-10 nm, the powder water absorption rate of the AlN filler powder coated with the silica coating layer is less than 1%, and the tap density is 0.7-1.8 g / cm 3 The zeta potential that characterizes the dispersion is -30~-50mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 20-70MPa, the tensile strength is about 5-25MPa, the elastic modulus is usually 0.5-3GPa, the flexural strength can reach 20-60MPa, and the hardness is usually 10-90 Shore A.

[0023] Compared with the prior art, the above technical solution has at least the following beneficial effects:

[0024] The above scheme, the present invention proposes a method for preparing aluminum nitride powder with a silicon dioxide coating layer, which can solve the problem that the surface of aluminum nitride filler powder in the prior art is generally modified to prepare a hydrophobic coating to resist hydrolysis. Most of the components of the hydrophobic coating are organic matter or polymers, and it is not considered that the modification is to enhance the mechanical strength of the aluminum nitride filler, improve its compression, tension and bending resistance, and it is not considered that the thickness uniformity, thickness control, durability, stability and other properties of the modified coating are difficult to control. Technical problems.

[0025] The present invention can achieve uniform coating and thickness control on the surface of AlN filler powder through fluidization modification technology, ensuring that each particle can obtain a silicon dioxide coating layer with uniform thickness uniformly distributed by silicon dioxide particles, thereby improving the overall performance of the material.

[0026] The fluidized modification technology of the present invention can ensure a strong chemical bond between the silica coating layer and the AlN filler powder by covalent bonding, which not only improves the adhesion between the two, but also improves the overall durability and performance stability of the filler.

[0027] The silicon dioxide coating layer with uniform thickness and uniform particle distribution of the present invention can improve the hydrolysis resistance of the AlN filler powder under high temperature and high humidity conditions, making it perform better in extreme environments.

[0028] The present invention can flexibly and accurately control the thickness and properties of the silicon dioxide coating layer by adjusting the process parameters in the fluidized modification process to meet different industrial application requirements.

[0029] The present invention obtains modified AlN filler powder which can enhance the mechanical strength, compressive strength, tensile strength, bending strength and other properties of aluminum nitride filler by modifying the surface of AlN filler powder, thereby broadening the application scope and improving the use value.

[0030] In summary, compared with other traditional methods, the method of the present invention can achieve uniform coating and thickness control on the surface of AlN filler powder through fluidization modification technology, and can enhance its mechanical strength, compressive strength and flexural strength and other properties by compounding with an organic matrix into a thermal interface material; improve the dispersibility of the filler powder, facilitate subsequent processing and molding, be simple and easy to operate, reduce dependence on harmful solvents, be green and environmentally friendly, low cost, high efficiency, and be conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 It is a process flow chart of a method for preparing aluminum nitride powder with a silicon dioxide coating layer of the present invention;

[0033] Figure 2 This is a SEM image of AlN filler powder coated with silicon dioxide prepared by a method for preparing aluminum nitride powder with a silicon dioxide coating layer in Example 1 of the present invention;

[0034] Figure 3 This is a SEM image of AlN filler powder coated with silicon dioxide prepared by a method for preparing aluminum nitride powder with a silicon dioxide coating layer in Example 2 of the present invention;

[0035] Figure 4 This is a SEM image of AlN filler powder coated with silicon dioxide prepared by a method for preparing aluminum nitride powder with a silicon dioxide coating layer in Example 3 of the present invention;

[0036] Figure 5 This is a SEM image of AlN filler powder coated with silicon dioxide prepared by a method for preparing aluminum nitride powder with a silicon dioxide coating layer in Example 4 of the present invention;

[0037] Figure 6 This is a SEM image of AlN filler powder coated with silicon dioxide prepared by a method for preparing aluminum nitride powder with a silicon dioxide coating layer in Example 5 of the present invention;

[0038] Figure 7 This is a SEM image of AlN filler powder coated with silicon dioxide prepared by the method for preparing aluminum nitride powder with a silicon dioxide coating layer according to Example 6 of the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is described below in conjunction with the accompanying drawings.

[0040] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.

[0041] In the embodiments of the present invention, "image" and "picture" may sometimes be used interchangeably. It should be noted that when the distinction between them is not emphasized, the meanings they intend to express are consistent.

[0042] In the embodiments of the present invention, sometimes a subscript such as W1 may be written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are the same.

[0043] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0044] A method for preparing aluminum nitride powder with a silicon dioxide coating layer, the method for preparing aluminum nitride powder with a silicon dioxide coating layer is combined with Figure 1 Follow these steps:

[0045] S1. Surface pretreatment of AlN filler powder: weigh an appropriate amount of high-purity AlN filler powder, mix the AlN filler powder with anhydrous ethanol to prepare an AlN suspension, place the suspension in an ultrasonic cleaning machine and start a cleaning process while ultrasonicating and stirring, and then perform vacuum filtration to obtain AlN filler wet powder;

[0046] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment to obtain AlN filler powder with clean surface;

[0047] S3, silica modification treatment of AlN filler powder: placing the cleaned AlN filler powder in S2 in a fluidized bed reactor, turning on a heating device to control the required fluidization temperature, introducing a silica precursor into the fluidized bed reactor by spraying and reacting under an inert atmosphere, and then introducing an oxygen source into the fluidized bed reactor through a gas input system to carry out a surface covalent bonding reaction of the AlN filler powder under an inert atmosphere to obtain silica-modified AlN filler powder;

[0048] S4, repeat and cycle S3: repeat the silica modification treatment of the AlN filler powder of S3 to the silica-modified AlN filler powder of S3, forming a silica coating layer of different thicknesses, uniform distribution and stable performance on the surface of the AlN filler powder, and obtaining AlN filler powder coated with the silica coating layer.

[0049] In particular, the particle size of the AlN filler powder in S1 is 1-20 μm; the purity is 99.90-99.99%.

[0050] In particular, the mass ratio of AlN filler powder to anhydrous ethanol in S1 is 1:(1.58-4.74).

[0051] In particular, the ultrasonic parameters of the cleaning process in S1 are set as follows: ultrasonic temperature 25-35° C., and ultrasonic duration 10-20 min.

[0052] In particular, the drying temperature in S2 is 50-75° C., the drying time is 2-4 hours, and the AlN filler powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 1-20 μm and a water content of 0.05-0.2%.

[0053] Particularly, the silicon dioxide precursor in S3 is at least one of silicon tetrachloride, dimethylsilane and triethoxysilane, and the flow rate of the silicon dioxide precursor is 0.3-1 L / min, and the time is 3-6 min.

[0054] Particularly, the oxygen source in S3 is at least one of oxygen and water, and the oxygen source is introduced at a flow rate of 0.3-1 L / min for 3-6 min.

[0055] In particular, the inert atmosphere in S3 is at least one of nitrogen and argon, the time of inert gas introduction lasts from the beginning to the end of fluidization, and the flow rate of inert gas introduction is 0.2-2L / min; the fluidization treatment temperature is 120-200°C, and the fluidization time is 100-980min.

[0056] In particular, the silicon dioxide precursor and the oxygen source in S3 are successively introduced into the fluidized bed reactor through different independent delivery systems.

[0057] In particular, the number of cycles mentioned in S4 is 15-80, the thickness of the silica coating layer is controlled at 3-10 nm, the powder water absorption rate of the AlN filler powder coated with the silica coating layer is <1%, and the tap density is 0.7-1.8 g / cm 3The zeta potential that characterizes the dispersion is -30~-50mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 20-70MPa, the tensile strength is about 5-25MPa, the elastic modulus is usually 0.5-3GPa, the flexural strength can reach 20-60MPa, and the hardness is usually 10-90 Shore A.

[0058] Example 1

[0059] A method for preparing aluminum nitride powder having a silicon dioxide coating layer, the method for preparing aluminum nitride powder having a silicon dioxide coating layer comprises the following steps:

[0060] S1. Surface pretreatment of AlN filler powder: weigh 1 kg of AlN filler powder with a purity of 99.90% and a particle size of 1 μm, mix the AlN filler powder and anhydrous ethanol in a mass ratio of 1:4.74 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 25°C, the ultrasonic time is 10 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0061] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 50°C for 4 hours to obtain AlN filler powder with a clean surface; the AlN filler powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 1 μm and a water content of 0.2%;

[0062] S3, silica modification treatment of AlN filler powder: the cleaned AlN filler powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 120°C, silicon tetrachloride is introduced into the fluidized bed reactor by spraying and reacted in a nitrogen atmosphere, the flow rate of which is 0.3L / min, and the time is 6min; then oxygen is introduced into the fluidized bed reactor through a gas input system to carry out surface covalent bonding reaction of the AlN filler powder under a nitrogen environment, the flow rate of oxygen introduced into the fluidized bed reactor is 0.3L / min, the time is 3min, the flow rate of nitrogen introduced is 0.2L / min, the fluidization treatment temperature is 120°C, and the fluidization time is 100min, to obtain silica-modified AlN filler powder; wherein: the silica precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0063] S4, repeat and cycle S3: repeat the silica modification treatment of the AlN filler powder of S3, the number of cycles is 15, the whole fluidization process duration is 100 minutes, and a silica coating layer with a thickness of 3 mm, uniform distribution and stable performance is formed on the surface of the AlN filler powder to obtain AlN filler powder coated with the silica coating layer.

[0064] The thickness of the silicon dioxide coating layer prepared in this embodiment is controlled at 3 nm. Figure 2 As shown in Figure 2, the AlN filler powder coated with the silica coating has a water absorption rate of 0.95% and a tap density of 0.7 g / cm 3 The zeta potential that characterizes the dispersion is -30mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 20MPa, the tensile strength is about 5MPa, the elastic modulus is usually 0.5GPa, the flexural strength can reach 20MPa, and the hardness is usually 10 Shore A.

[0065] Example 2

[0066] A method for preparing aluminum nitride powder having a silicon dioxide coating layer, the method for preparing aluminum nitride powder having a silicon dioxide coating layer comprises the following steps:

[0067] S1. Surface pretreatment of AlN filler powder: weigh 1 kg of AlN filler powder with a purity of 99.92% and a particle size of 3 μm, mix the AlN filler powder and anhydrous ethanol in a mass ratio of 1:4 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 30°C, the ultrasonic time is 10 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0068] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 55°C for 3.5 hours to obtain AlN filler powder with a clean surface; the AlN filler powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 3 μm and a water content of 0.15%;

[0069] S3, silica modification treatment of AlN filler powder: the cleaned AlN filler powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 150°C, and the silica precursor of silicon tetrachloride is introduced into the fluidized bed reactor by spraying and reacted under a nitrogen atmosphere, the flow rate of which is 1L / min, and the time is 6min; then oxygen is introduced into the fluidized bed reactor through a gas input system to carry out a surface covalent bonding reaction of the AlN filler powder under a nitrogen environment, the flow rate of oxygen introduced into the fluidized bed reactor is 1L / min, the time is 6min, the flow rate of nitrogen introduced is 0.7L / min, the fluidization treatment temperature is 150°C, and the fluidization time is 980min, to obtain silica-modified AlN filler powder; wherein: the silica precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0070] S4, repeat and cycle S3: repeat the silica modification treatment of the AlN filler powder of S3, the number of cycles is 80, the whole fluidization process duration is 980 minutes, and a silica coating layer with a thickness of 10 mm, uniform distribution and stable performance is formed on the surface of the AlN filler powder to obtain AlN filler powder coated with the silica coating layer.

[0071] The thickness of the silicon dioxide coating layer prepared in this embodiment is controlled at 10 nm. Figure 3 As shown in Figure 2, the AlN filler powder coated with the silica coating has a water absorption rate of 0.5% and a tap density of 1.8 g / cm 3 The zeta potential that characterizes the dispersion is -50mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 70MPa, the tensile strength is about 25MPa, the elastic modulus is usually 3GPa, the flexural strength can reach 60MPa, and the hardness is usually 90 Shore A.

[0072] Example 3

[0073] A method for preparing aluminum nitride powder having a silicon dioxide coating layer, the method for preparing aluminum nitride powder having a silicon dioxide coating layer comprises the following steps:

[0074] S1. Surface pretreatment of AlN filler powder: weigh 1 kg of aluminum nitride powder with a purity of 99.94% and a particle size of 5 μm, mix the AlN powder and anhydrous ethanol in a mass ratio of 1:3.5 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 30°C, the ultrasonic time is 15 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0075] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment, the drying temperature is 60°C, the time is 3 hours, and the AlN filler powder with a clean surface is obtained; the AlN filler powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 5 μm and a water content of 0.1%;

[0076] S3, silica modification treatment of AlN filler powder: the cleaned AlN filler powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 165°C, and the silica precursor of dimethylsilane is introduced into the fluidized bed reactor by spraying and reacted under an inert atmosphere, the flow rate of which is 0.9L / min, and the time is 5min; then, oxygen is introduced into the fluidized bed reactor through a gas input system to carry out surface covalent bonding reaction of the AlN filler powder under a nitrogen environment, the flow rate of oxygen introduced into the fluidized bed reactor is 0.9L / min, the fluidization treatment temperature is 165°C, and the fluidization time is 500min, to obtain silica-modified AlN filler powder; wherein: the silica precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0077] S4, repeat and cycle S3: Repeat the silica modification treatment of the AlN filler powder of S3 for 60 cycles, forming a silica protective layer of different thicknesses, uniform distribution and stable performance on the surface of the AlN filler powder, and obtaining AlN filler powder coated with a silica coating layer.

[0078] The thickness of the silicon dioxide coating layer prepared in this embodiment is controlled at 8 nm. Figure 4 As shown in Figure 2, the AlN filler powder coated with the silica coating has a water absorption rate of 0.6% and a tap density of 1.6 g / cm 3 The zeta potential that characterizes the dispersion is -45mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 65MPa, the tensile strength is about 20MPa, the elastic modulus is usually 2GPa, the flexural strength can reach 50MPa, and the hardness is usually 80 Shore A.

[0079] Example 4

[0080] A method for preparing aluminum nitride powder having a silicon dioxide coating layer, the method for preparing aluminum nitride powder having a silicon dioxide coating layer comprises the following steps:

[0081] S1. Surface pretreatment of AlN filler powder: weigh 1 kg of aluminum nitride powder with a purity of 99.95% and a particle size of 6 μm, mix the AlN powder and anhydrous ethanol in a mass ratio of 1:3 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 30°C, the ultrasonic time is 12 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0082] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 65°C for 2.5 hours to obtain AlN filler powder with a clean surface; the AlN filler powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 6 μm and a water content of 0.08%;

[0083] S3, surface modification of AlN filler powder: the cleaned AlN filler powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 175°C, and the silicon dioxide precursor of dimethylsilane is introduced into the fluidized bed reactor by spraying and reacted under an inert atmosphere, the flow rate of which is 0.7L / min, and the time is 5min; then, oxygen is introduced into the fluidized bed reactor through a gas input system to carry out a surface covalent bonding reaction of the AlN filler powder in an inert gas environment of at least one of nitrogen and argon, the flow rate of oxygen introduced into the fluidized bed reactor is 0.7L / min, the time is 5min, the flow rate of inert gas introduced is 1.2L / min, the fluidization treatment temperature is 175°C, and the fluidization time is 420min, to obtain a surface modified AlN filler powder; wherein: the silicon dioxide precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0084] S4, repeat and cycle S3: Repeat the surface modification treatment of the AlN filler powder in S3 for 40 cycles, forming a silica coating layer of different thicknesses, uniform distribution and stable performance on the surface of the AlN filler powder, and obtaining an AlN filler powder coated with a silica coating layer.

[0085] The thickness of the silicon dioxide coating layer prepared in this embodiment is controlled at 6 nm. Figure 5 As shown in Figure 2, the water absorption rate of the AlN filler powder coated with the silica coating layer is 0.4%, and the tap density is 1.4 g / cm 3 The zeta potential that characterizes the dispersion is -40mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 60MPa, the tensile strength is about 15MPa, the elastic modulus is usually 1.5GPa, the flexural strength can reach 45MPa, and the hardness is usually 70 Shore A.

[0086] Example 5

[0087] A method for preparing aluminum nitride powder having a silicon dioxide coating layer, the method for preparing aluminum nitride powder having a silicon dioxide coating layer comprises the following steps:

[0088] S1. Surface pretreatment of AlN filler powder: weigh 1 kg of aluminum nitride powder with a purity of 99.97% and a particle size of 8 μm, mix AlN powder and anhydrous ethanol in a mass ratio of 1:2.5 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 35°C, the ultrasonic time is 15 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0089] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 70°C for 2 hours to obtain AlN filler powder with a clean surface; the AlN filler powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 8 μm and a water content of 0.06%;

[0090] S3, surface modification of AlN filler powder: the cleaned AlN filler powder in S2 is placed in a fluidized bed reactor; the heating device is turned on to control the required fluidization temperature of 185°C, and the silicon dioxide precursor of aluminum triacetylacetonate is introduced into the fluidized bed reactor by spraying and reacted under an inert atmosphere, the flow rate of which is 0.5 L / min, and the time is 4 min; then oxygen is introduced into the fluidized bed reactor through a gas input system to carry out surface covalent bonding reaction of the AlN filler powder in an inert gas environment of at least one of nitrogen and argon, the flow rate of oxygen introduced into the fluidized bed reactor is 0.5 L / min, the time is 4 min, the flow rate of inert gas introduced is 1.8 L / min, the fluidization treatment temperature is 185°C, and the fluidization time is 260 min, to obtain surface modified AlN filler powder; wherein: the silicon dioxide precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0091] S4, repeat and cycle S3: Repeat the surface modification treatment of the AlN filler powder in S3 for 30 cycles, forming a silica coating layer of different thicknesses, uniform distribution and stable performance on the surface of the AlN filler powder to obtain AlN filler powder coated with the silica coating layer.

[0092] The thickness of the silicon dioxide coating layer prepared in this embodiment is controlled at 5 nm. Figure 6 As shown in Figure 2, the water absorption rate of the AlN filler powder coated with the silica coating layer is 0.3%, and the tap density is 1.0 g / cm 3The zeta potential characterizing the dispersion is -35mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 53MPa, the tensile strength is about 13MPa, the elastic modulus is usually 1.2GPa, the flexural strength can reach 40MPa, and the hardness is usually 60 Shore A.

[0093] Example 6

[0094] A method for preparing aluminum nitride powder having a silicon dioxide coating layer, the method for preparing aluminum nitride powder having a silicon dioxide coating layer comprises the following steps:

[0095] S1. Surface pretreatment of AlN filler powder: weigh 1 kg of aluminum nitride powder with a purity of 99.99% and a particle size of 10 μm, mix the AlN powder and anhydrous ethanol in a mass ratio of 1:1.58 to form an AlN suspension, place the suspension in an ultrasonic cleaning machine and start ultrasonic cleaning while stirring, the ultrasonic temperature is 35°C, the ultrasonic time is 20 min, and then vacuum filtration is performed to obtain AlN filler wet powder;

[0096] S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment at a temperature of 75°C for 2 hours to obtain AlN filler powder with a clean surface; the AlN filler powder with a clean surface is spherical or quasi-spherical in shape, with a particle size of 10 μm and a water content of 0.02%;

[0097] S3, surface modification of AlN filler powder: place the cleaned AlN filler powder in S2 in a fluidized bed reactor; turn on the heating device to control the required fluidization temperature of 200°C, introduce the silica precursor of triethoxysilane into the fluidized bed reactor by spraying and react under an inert atmosphere, the flow rate of introduction is 0.4L / min, and the time is 5min; then introduce oxygen into the fluidized bed reactor through the gas input system to carry out surface covalent bonding reaction of the AlN filler powder in an inert gas environment of at least one of nitrogen and argon, the flow rate of oxygen introduced into the fluidized bed reactor is 0.4L / min, the time is 5min, the flow rate of inert gas introduction is 2L / min, the fluidization temperature is 200°C, and the fluidization time is 220min, to obtain surface modified AlN filler powder; wherein: the silica precursor and the oxygen source are successively introduced into the fluidized bed reactor through different independent conveying systems;

[0098] S4, repeat and cycle S3: Repeat the surface modification treatment of the AlN filler powder in S3 for 20 cycles, forming a silica coating layer of different thicknesses, uniform distribution and stable performance on the surface of the AlN filler powder, and obtaining an AlN filler powder coated with a silica coating layer.

[0099] The thickness of the silicon dioxide coating layer prepared in this embodiment is controlled at 4 nm. Figure 7 As shown in Figure 2, the water absorption rate of the AlN filler powder coated with the silica coating layer is 0.1%, and the tap density is 0.7 g / cm 3 The zeta potential that characterizes the dispersion is -30mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 30MPa, the tensile strength is about 8MPa, the elastic modulus is usually 0.9GPa, the flexural strength can reach 30MPa, and the hardness is usually 40 Shore A.

[0100] The above scheme, the present invention proposes a method for preparing aluminum nitride powder with a silicon dioxide coating layer, which can solve the problem that the surface of aluminum nitride filler powder in the prior art is generally modified to prepare a hydrophobic coating to resist hydrolysis. Most of the components of the hydrophobic coating are organic matter or polymers, and it is not considered that the modification is to enhance the mechanical strength of the aluminum nitride filler, improve its compression, tension and bending resistance, and it is not considered that the thickness uniformity, thickness control, durability, stability and other properties of the modified coating are difficult to control. Technical problems.

[0101] The present invention can achieve uniform coating and thickness control on the surface of AlN filler powder through fluidization modification technology, ensuring that each particle can obtain a silicon dioxide coating layer with uniform thickness uniformly distributed by silicon dioxide particles, thereby improving the overall performance of the material.

[0102] The fluidized modification technology of the present invention can ensure a strong chemical bond between the silica coating layer and the AlN filler powder by covalent bonding, which not only improves the adhesion between the two, but also improves the overall durability and performance stability of the filler.

[0103] The silicon dioxide coating layer with uniform thickness and uniform particle distribution of the present invention can improve the hydrolysis resistance of the AlN filler powder under high temperature and high humidity conditions, making it perform better in extreme environments.

[0104] The present invention can flexibly and accurately control the thickness and properties of the silicon dioxide coating layer by adjusting the process parameters in the fluidized modification process to meet different industrial application requirements.

[0105] The present invention obtains modified AlN filler powder which can enhance the mechanical strength, compressive strength, tensile strength, bending strength and other properties of aluminum nitride filler by modifying the surface of AlN filler powder, thereby broadening the application scope and improving the use value.

[0106] In summary, compared with other traditional methods, the method of the present invention can achieve uniform coating and thickness control on the surface of AlN filler powder through fluidization modification technology, and can enhance its mechanical strength, compressive strength and flexural strength and other properties by compounding with an organic matrix into a thermal interface material; improve the dispersibility of the filler powder, facilitate subsequent processing and molding, be simple and easy to operate, reduce dependence on harmful solvents, be green and environmentally friendly, low cost, high efficiency, and be conducive to large-scale industrial production and promotion.

[0107] It should be understood that the term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship, but it may also indicate an "and / or" relationship. Please refer to the context for specific understanding.

[0108] In the present invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b, or c can mean: a, b, c, ab, ac, bc, or abc, where a, b, and c can be single or multiple.

[0109] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0110] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing aluminum nitride powder having a silicon dioxide coating layer, characterized in that: The method for preparing the aluminum nitride powder having a silicon dioxide coating layer comprises the following steps: S1. Surface pretreatment of AlN filler powder: weigh an appropriate amount of high-purity AlN filler powder, mix the AlN filler powder with anhydrous ethanol to prepare an AlN suspension, place the suspension in an ultrasonic cleaning machine and start a cleaning process while ultrasonicating and stirring, and then perform vacuum filtration to obtain AlN filler wet powder; S2, drying treatment: placing the wet AlN filler powder in S1 in a drying oven for drying treatment to obtain AlN filler powder with clean surface; S3, silica modification treatment of AlN filler powder: placing the cleaned AlN filler powder in S2 in a fluidized bed reactor, turning on a heating device to control the required fluidization temperature, introducing a silica precursor into the fluidized bed reactor by spraying and reacting under an inert atmosphere, and then introducing an oxygen source into the fluidized bed reactor through a gas input system to carry out a surface covalent bonding reaction of the AlN filler powder under an inert atmosphere to obtain silica-modified AlN filler powder; S4, repeat and cycle S3: repeat the silica modification treatment of the AlN filler powder of S3 to the silica-modified AlN filler powder of S3, forming a silica coating layer of different thicknesses, uniform distribution and stable performance on the surface of the AlN filler powder, and obtaining AlN filler powder coated with the silica coating layer.

2. The method for preparing aluminum nitride powder having a silicon dioxide coating layer according to claim 1, characterized in that: The particle size of AlN filler powder in S1 is 1-20 μm; the purity is 99.90-99.99%.

3. The method for preparing aluminum nitride powder with a silicon dioxide coating layer according to claim 1, characterized in that: The mass ratio of AlN filler powder to anhydrous ethanol in S1 is 1:(1.58-4.74).

4. The method for preparing aluminum nitride powder with a silicon dioxide coating layer according to claim 1, characterized in that: The ultrasonic parameters of the cleaning process in S1 are set as follows: ultrasonic temperature 25-35°C, ultrasonic time 10-20min.

5. The method for preparing aluminum nitride powder with a silicon dioxide coating layer according to claim 1, characterized in that: The drying temperature in S2 is 50-75°C for 2-4 hours. The AlN filler powder with cleaned surface is spherical or quasi-spherical in shape, with a particle size of 1-20 μm and a water content of 0.05-0.2%.

6. The method for preparing aluminum nitride powder with a silicon dioxide coating layer according to claim 1, characterized in that: The silicon dioxide precursor in S3 is at least one of silicon tetrachloride, dimethylsilane and triethoxysilane, and the flow rate of the silicon dioxide precursor is 0.3-1 L / min, and the time is 3-6 min.

7. The method for preparing aluminum nitride powder with a silicon dioxide coating layer according to claim 1, characterized in that: The oxygen source in S3 is at least one of oxygen and water, and the oxygen source is introduced at a flow rate of 0.3-1 L / min for 3-6 min.

8. The method for preparing aluminum nitride powder with a silicon dioxide coating layer according to claim 1, characterized in that: The inert atmosphere in S3 is at least one of nitrogen and argon. The inert gas is introduced from the beginning to the end of fluidization, and the flow rate of the inert gas is 0.2-2L / min. The fluidization treatment temperature is 120-200°C, and the fluidization time is 100-980min.

9. The method for preparing aluminum nitride powder with a silicon dioxide coating layer according to claim 1, characterized in that: In S3, the silica precursor and the oxygen source enter the fluidized bed reactor successively through different independent delivery systems.

10. The method for preparing aluminum nitride powder with a silicon dioxide coating layer according to claim 1, characterized in that: The number of cycles mentioned in S4 is 15-80, the thickness of the silica coating layer is controlled at 3-10 nm, the powder water absorption rate of the AlN filler powder coated with the silica coating layer is <1%, and the tap density is 0.7-1.8 g / cm 3 The zeta potential that characterizes the dispersion is -30~-50mv. The compressive strength of the thermal interface material composited with the organic matrix is ​​in the range of 20-70MPa, the tensile strength is about 5-25MPa, the elastic modulus is usually 0.5-3GPa, the flexural strength can reach 20-60MPa, and the hardness is usually 10-90 ShoreA.

Citation Information

Patent Citations

  • Preparation method of aluminum nitride powder used for heat conduction filler

    CN106586983A

  • Method for producing silicon-containing oxide-coated aluminum nitride particles and method for producing exoergic resin composition

    CN113474411A

  • Silicon dioxide coating layer and preparation method thereof

    CN115011143A

  • Preparation method of silicon dioxide nano-layer coated gamma-aluminium oxide powder material

    CN104275171A

  • Coating modification method and application of aluminum nitride powder

    CN115637063A